Near-infrared fluorescent glass for bioimaging and preparation method and device thereof

CN118702408BActive Publication Date: 2026-10-20SHANGHAI INST OF OPTICS & FINE MECHANICS CHINESE ACAD OF SCI
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410959811.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-17
Publication Date
2026-10-20
Estimated Expiration
2044-07-17

AI Technical Summary

Technical Problem

然而粉体材料易受到外部环境影响而存在团聚,化学性能不稳定,需要成型来使用等问题

Benefits of technology

[0022]本发明公开的用于生物成像的宽带近红外发光硼酸盐玻璃,在碳保护的还原气氛下高温熔化制备,所选原料价格低廉,制备过程简单。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118702408B_ABST
    Figure CN118702408B_ABST
Patent Text Reader

Abstract

The application provides a near-infrared fluorescent glass for bio-imaging, a preparation method and a device. The molar percentage of each component of the glass is as follows: 20-50 mol% of MO, 0-40 mol% of MF2, 0-40 mol% of MSO4, 10-40 mol% of B2O3, and 10-30 mol% of Al2O3, wherein M is one or more of alkaline earth metals Ca, Sr or Ba, MO is alkaline earth metal oxide, MF2 is alkaline earth metal fluoride, and MSO4 is alkaline earth metal sulfate. The glass is prepared by high-temperature melting under a carbon-protected reducing atmosphere. Under ultraviolet excitation, the glass can generate a near-infrared broadband emission spectrum covering 500-1200 nm and having a full width at half maximum of 228 nm. The glass has stable physical and chemical properties, low raw material cost, large emission spectrum half-width, and can be prepared into a near-infrared fluorescent optical fiber. In combination with a 365 nm blue light LED, the device can realize non-destructive imaging of human finger blood vessels, and has good application prospects in the field of non-destructive detection of organic components and bio-imaging.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of near-infrared luminescent materials, and particularly to a broadband near-infrared luminescent borate glass for bioimaging applications, its preparation method, and devices. Background Technology

[0002] Compared to the visible and mid-infrared bands, near-infrared spectroscopy is widely used in fields such as biological imaging, chemical composition analysis, night vision, medicine, and optoelectronic devices due to its non-invasive detection characteristics.

[0003] A good near-infrared light source needs to have a sufficiently broad near-infrared spectrum. Traditional near-infrared light sources such as incandescent lamps and halogen lamps have broadband emission and high brightness, but they suffer from drawbacks such as high energy consumption and large size. Near-infrared light-emitting diodes (NIRLEDs) are low in energy consumption, environmentally friendly, and miniaturized, but their emission peak coverage is narrow. Currently, phosphor-converted near-infrared LEDs (NIRpc-LEDs) have become a popular near-infrared light source due to their low energy consumption, environmental friendliness, and miniaturization.

[0004] In the known patent CN 113025328A, Li Chengyu et al. provided a La x M 4-x-y-z Sc y (BO3)4Cl:zCr 3 + The preparation method of phosphors covers the emission bandgap of 650–1200 nm. However, powder materials are susceptible to external environmental influences, resulting in agglomeration, unstable chemical properties, and the need for molding before use. Currently, in the known patent CN 116715441A, Xia Zhiguo et al. mentioned replacing traditional phosphor materials with solid materials such as glass or glass-ceramics to overcome the defects of powder materials. The biggest advantage of glass materials is that they can be drawn into optical fibers, improving spectral intensity and ease of use.

[0005] As can be seen from publicly available information, near-infrared luminescent glass materials are scarce compared to phosphor materials. Therefore, developing novel near-infrared glass materials with high physicochemical stability that can be effectively excited by blue LEDs is of great significance. The near-infrared luminescent glass disclosed in this invention adds a new member to this research field. Furthermore, the near-infrared light source (NIR gc-LEDs) assembled with 365nm blue LEDs overcomes the shortcomings of powder materials, exhibiting advantages such as low cost, high stability, good transparency, and simple fabrication process. Summary of the Invention

[0006] The purpose of this invention is to provide a near-infrared fluorescent glass for bioimaging, its preparation method, and the device thereof. This glass has the characteristics of wide near-infrared fluorescence spectral line, transparency, stable physicochemical properties, low price, good stability, and can be drawn into optical fibers.

[0007] The technical solution adopted in this invention is as follows: a near-infrared fluorescent glass for bioimaging, wherein the glass composition has the following molar percentages: 20-50 mol% MO, 0-40 mol% MF2, 0-40 mol% MSO4, 10-40 mol% B2O3, and 10-30 mol% Al2O3, wherein MO is one or more alkaline earth metal oxides, MF2 is one or more alkaline earth metal fluorides, and MSO4 is one or more alkaline earth metal sulfates.

[0008] Furthermore, the glass composition comprises the following molar percentages: 49.3 mol% BaO, 0.7 mol% BaSO4, 40 mol% B2O3, and 10 mol% Al2O3.

[0009] Furthermore, the glass composition comprises the following molar percentages: 20 mol% BaO, 30 mol% BaF2, 40 mol% B2O3, and 10 mol% Al2O3.

[0010] Furthermore, the MO alkaline earth metal oxide is one or more of CaO, SrO, or BaO.

[0011] Furthermore, the MF2 alkaline earth metal fluoride is one or more of CaF2, SrF2, or BaF2.

[0012] Furthermore, the MSO4 alkaline earth metal sulfate is one or more of CaSO4, SrSO4, or BaSO4.

[0013] The present invention also provides a method for preparing the above-mentioned near-infrared fluorescent glass for bioimaging, comprising the following steps:

[0014] ① According to the borate glass composition and molar percentage of claim 1, calculate the mass of each glass component, accurately weigh each raw material, wherein the MO can be introduced by MCO3, the B2O3 can be introduced by B2O3 or H3BO3, and the Al2O3 can be introduced by Al(OH)3 or Al2O3; grind the weighed raw materials in an agate mortar and mix them evenly to form a mixture.

[0015] ② Take the mixture and put it into a high-temperature furnace. Heat it from room temperature to 1000℃~1300℃ and melt it for 10-60 minutes under a reducing atmosphere with carbon protection. After taking out the glass, quickly pour it onto a graphite plate to obtain a transparent glass sample.

[0016] ③ The obtained glass sample is transferred to a muffle furnace at 470℃~500℃ for annealing. After holding at the temperature for 3~5 hours, it is naturally cooled to room temperature with the furnace. After it is completely cooled, the glass is taken out.

[0017] The reducing atmosphere for carbon protection is achieved through the following methods:

[0018] Using the nested crucible method, the raw material is placed in a corundum crucible, and then a covered corundum crucible containing carbon powder or graphite powder is placed on the outside.

[0019] Using the nested crucible method, the raw material is placed in a graphite crucible and then covered with a corundum crucible.

[0020] Place the raw materials directly into a covered graphite crucible.

[0021] Technical effects of the present invention:

[0022] The broadband near-infrared luminescent borate glass for bioimaging disclosed in this invention is prepared by high-temperature melting under a carbon-protected reducing atmosphere. The selected raw materials are inexpensive and the preparation process is simple.

[0023] The borate glass of this invention possesses characteristics such as broad near-infrared fluorescence linewidth, transparency, stable physicochemical properties, low cost, good stability, and the ability to be drawn into optical fibers. The glass sample prepared by this invention exhibits strong near-infrared fluorescence, with an emission spectrum showing a broadband emission peak at a center wavelength of 740 nm and a full width at half maximum (FWHM) of 228 nm. Combined with a device composed of 365 nm blue LEDs (NIR gc-LEDs), it can achieve non-destructive imaging of blood vessels in the human finger, showing great application potential in fields such as organic component detection and bioimaging. Attached Figure Description

[0024] Figure 1 The excitation and emission spectra of Example 1# in this invention are shown below;

[0025] Figure 2 The excitation and emission spectra of Example 2# in this invention are shown below;

[0026] Figure 3 The diagram and physical image show the GC-LED device composed of Example 1# and a 365nm blue LED in this invention.

[0027] Figure 4 This is an image of a human finger created by a gc-LED device composed of Example 1# and a 365nm blue LED. Detailed Implementation

[0028] The specific technical solutions in the embodiments of the present invention will be described below. The parts described below are not all examples of the present invention. Other examples that are not inventive and are based on the present invention are all within the protection scope of the present invention.

[0029] The glass composition of a specific embodiment of the near-infrared fluorescent glass for bioimaging of the present invention is as follows:

[0030]

[0031]

[0032] Table 1: Glass composition of Examples 1-15#

[0033] Example 1#:

[0034] The preparation process of Example 1 is as follows:

[0035] Mass (g) 11.865 0.199 6.033 1.903

[0036] Table 2: Composition of matrix glass in Example 1

[0037] First, according to the matrix glass composition in Table 2, weigh 20g of the required raw materials, including BaCO3 (11.865g) (MO introduced from BaCO3), BaSO4 (0.199g) (MSO4 introduced from BaSO4), H3BO3 (6.033g) (B2O3 introduced from H3BO3), and Al(OH)3 (1.903g) (Al2O3 introduced from Al(OH)3). Mix all raw materials thoroughly in an agate mortar. After mixing, place the raw materials in a graphite crucible and melt them in a silicon carbide rod furnace at 1200℃ for 10 minutes. Pour the clear glass melt onto a graphite plate and press it into a glass sheet. Transfer the obtained glass to an annealing furnace at 470℃ for 3 hours. After cooling to room temperature in the furnace, remove the glass to obtain an orange-red transparent borate glass. Under ultraviolet light excitation, the prepared glass sample exhibited strong near-infrared fluorescence. The emission spectrum obtained using an FLS1000 fluorescence spectrometer showed a broadband emission peak with a center wavelength of 740 nm and a full width at half maximum (FWHM) of 228 nm. (See below.) Figure 3 This device, composed of 365nm blue LEDs (NIR gc-LEDs) and combined with a near-infrared camera, enables non-invasive imaging of blood vessels in the human finger. The imaging effect is as follows... Figure 4 As shown, the distribution of blood vessels in a human finger can be clearly seen.

[0038] Example 2#:

[0039] The preparation process of Example 2 is as follows:

[0040] Mass (g) 5.023 6.695 6.296 1.986

[0041] Table 3: Composition of matrix glass in Example 2

[0042] First, according to the matrix glass composition in Table 3, weigh 20g of the required raw materials, including BaCO3 (5.023g) (MO introduced from BaCO3), BaF2 (6.695g) (MF2 introduced from BaF2), H3BO3 (6.296g) (B2O3 introduced from H3BO3), and Al(OH)3 (1.986g) (Al2O3 introduced from Al(OH)3). Mix all raw materials thoroughly in an agate mortar. After mixing, place the raw materials in a graphite crucible and melt them in a silicon carbide rod furnace at 1200℃ for 20 minutes. Pour the clear glass melt onto a graphite plate and press it into a glass sheet. Transfer the obtained glass to an annealing furnace at 470℃ for 3 hours. After cooling to room temperature in the furnace, remove the glass to obtain an orange-yellow transparent borate glass. Under ultraviolet light excitation, the prepared glass sample exhibits strong near-infrared fluorescence. The emission spectrum obtained by the FLS1000 fluorescence spectrometer is a broadband emission peak with a center wavelength of 730 nm and a full width at half maximum (FWHM) of 228 nm.

[0043] Example 3#:

[0044] The preparation process of Example 3 is as follows:

[0045] Mass (g) 11.741 0.278 4.268 3.713

[0046] Table 4: Composition of matrix glass in Example 3

[0047] First, according to the matrix glass composition in Table 4, weigh 20g of the required raw materials, including BaCO3 (11.741g) (MO introduced from BaCO3), BaSO4 (0.278g) (MSO4 introduced from BaSO4), H3BO3 (4.268g) (B2O3 introduced from H3BO3), and Al(OH)3 (3.713g) (Al2O3 introduced from Al(OH)3). Mix all raw materials thoroughly in an agate mortar. After mixing, place the raw materials in a graphite crucible and melt them in a silicon carbide rod electric furnace at 1000℃ for 60 minutes. Pour the clarified glass melt onto a graphite plate and press it into a glass sheet. Transfer the obtained glass to an annealing furnace at 480℃ for 3 hours. After cooling to room temperature in the furnace, remove the glass to obtain an orange-red transparent borate glass. Under ultraviolet light excitation, the prepared glass sample exhibits strong near-infrared fluorescence. The emission spectrum obtained by the FLS1000 fluorescence spectrometer is a broadband emission peak with a center wavelength of 740 nm and a full width at half maximum (FWHM) of 228 nm.

[0048] Example 4#:

[0049] The preparation process of Example 4 is as follows:

[0050]

[0051]

[0052] Table 5: Composition of matrix glass in Example 4

[0053] First, according to the matrix glass composition in Table 5, weigh 20g of the required raw materials, including CaCO3 (7.497g) (MO introduced from CaCO3), CaSO4 (1.133g) (MSO4 introduced from CaSO4), H3BO3 (6.176g) (B2O3 introduced from H3BO3), and Al(OH)3 (5.194g) (Al2O3 introduced from Al(OH)3). Mix all raw materials thoroughly in an agate mortar. After mixing, place the raw materials in a graphite crucible and melt them in a silicon carbide rod furnace at 1300℃ for 60 minutes. Pour the clear glass melt onto a graphite plate and press it into a glass sheet. Transfer the obtained glass to an annealing furnace at 480℃ for 5 hours. After cooling to room temperature in the furnace, remove the glass to obtain an orange-red transparent borate glass. Under ultraviolet light excitation, the prepared glass sample exhibits strong near-infrared fluorescence. The emission spectrum obtained by the FLS1000 fluorescence spectrometer is a broadband emission peak with a center wavelength of 740 nm and a full width at half maximum (FWHM) of 228 nm.

[0054] Example 5#:

[0055] The preparation process of Example 5 is as follows:

[0056] Mass (g) 6.396 2.175 3.952 7.477

[0057] Table 6: Composition of the matrix glass in Example 5

[0058] First, according to the matrix glass composition in Table 6, weigh 20g of the required raw materials, including CaCO3 (6.396g) (MO introduced from CaCO3), CaSO4 (2.175g) (MSO4 introduced from CaSO4), H3BO3 (3.952g) (B2O3 introduced from H3BO3), and Al(OH)3 (7.477g) (Al2O3 introduced from Al(OH)3). Mix all raw materials thoroughly in an agate mortar. After mixing, place the raw materials in a graphite crucible and melt them in a silicon carbide rod furnace at 1300℃ for 30 minutes. Pour the clear glass melt onto a graphite plate and press it into a glass sheet. Transfer the obtained glass to an annealing furnace at 490℃ for 4 hours. After cooling to room temperature in the furnace, remove the glass to obtain an orange-red transparent borate glass. Under ultraviolet light excitation, the prepared glass sample exhibits strong near-infrared fluorescence. The emission spectrum obtained by the FLS1000 fluorescence spectrometer is a broadband emission peak with a center wavelength of 740 nm and a full width at half maximum (FWHM) of 228 nm.

[0059] Example 6#:

[0060] The preparation process of Example 6 is as follows:

[0061] Mass (g) 7.622 4.742 1.596 6.040

[0062] Table 7: Composition of the matrix glass in Example 6

[0063] First, according to the matrix glass composition in Table 7, weigh 20g of the required raw materials, including SrCO3 (7.622g) (where MO is introduced from SrCO3), SrSO4 (4.742g) (where MSO4 is introduced from SrSO4), H3BO3 (1.596g) (where B2O3 is introduced from H3BO3), and Al(OH)3 (6.040g) (where Al2O3 is introduced from Al(OH)3). Mix all raw materials thoroughly in an agate mortar. After mixing, place the raw materials in a graphite crucible and melt them in a silicon carbide rod furnace at 1200℃ for 30 minutes. Pour the clear glass melt onto a graphite plate and press it into a glass sheet. Transfer the obtained glass to an annealing furnace at 500℃ for 5 hours. After cooling to room temperature in the furnace, remove the glass to obtain an orange-red transparent borate glass. Under ultraviolet light excitation, the prepared glass sample exhibits strong near-infrared fluorescence. The emission spectrum obtained by the FLS1000 fluorescence spectrometer is a broadband emission peak with a center wavelength of 740 nm and a full width at half maximum (FWHM) of 228 nm.

[0064] Example 7#:

[0065] The preparation process of Example 7 is as follows:

[0066] Mass (g) 1.926 9.586 6.453 2.035

[0067] Table 8: Composition of the matrix glass in Example 7

[0068] First, according to the matrix glass composition in Table 8, weigh 20g of the required raw materials, including SrCO3 (1.926g) (where MO is introduced from SrCO3), SrSO4 (9.586g) (where MSO4 is introduced from SrSO4), H3BO3 (6.453g) (where B2O3 is introduced from H3BO3), and Al(OH)3 (2.035g) (where Al2O3 is introduced from Al(OH)3). Mix all raw materials thoroughly in an agate mortar. After mixing, place the raw materials in a graphite crucible and melt them in a silicon carbide rod furnace at 1200℃ for 30 minutes. Pour the clear glass melt onto a graphite plate and press it into a glass sheet. Transfer the obtained glass to an annealing furnace at 500℃ for 5 hours. After cooling to room temperature in the furnace, remove the glass to obtain an orange-red transparent borate glass. Under ultraviolet light excitation, the prepared glass sample exhibits strong near-infrared fluorescence. The emission spectrum obtained by the FLS1000 fluorescence spectrometer is a broadband emission peak with a center wavelength of 740 nm and a full width at half maximum (FWHM) of 228 nm.

[0069] Example 8#:

[0070] The preparation process of Example 8 is as follows:

[0071] Mass (g) 7.522 2.228 6.286 3.964

[0072] Table 9: Composition of the matrix glass in Example 8

[0073] First, according to the matrix glass composition in Table 9, weigh 20g of the required raw materials, including BaCO3 (7.522g) (MO introduced from BaCO3), BaF2 (2.228g) (MF2 introduced from BaF2), H3BO3 (6.286g) (B2O3 introduced from H3BO3), and Al(OH)3 (3.964g) (Al2O3 introduced from Al(OH)3). Mix all raw materials thoroughly in an agate mortar. After mixing, place the raw materials in a graphite crucible and melt them in a silicon carbide rod electric furnace at 1200℃ for 10 minutes. Pour the clear glass melt onto a graphite plate and press it into a glass sheet. Transfer the obtained glass to an annealing furnace at 470℃ for 3 hours. After cooling to room temperature in the furnace, remove the glass to obtain an orange-yellow transparent borate glass. Under ultraviolet light excitation, the prepared glass sample exhibits strong near-infrared fluorescence. The emission spectrum obtained by the FLS1000 fluorescence spectrometer is a broadband emission peak with a center wavelength of 730 nm and a full width at half maximum (FWHM) of 228 nm.

[0074] Example 9#:

[0075] The preparation process of Example 9 is as follows:

[0076] Mass (g) 5.270 2.741 6.512 5.477

[0077] Table 10: Composition of the matrix glass in Example 9

[0078] First, according to the matrix glass composition in Table 10, weigh 20g of the required raw materials, including CaCO3 (5.270g) (MO introduced from CaCO3), CaF2 (2.741g) (MF2 introduced from CaF2), H3BO3 (6.512g) (B2O3 introduced from H3BO3), and Al(OH)3 (5.477g) (Al2O3 introduced from Al(OH)3). Mix all raw materials thoroughly in an agate mortar. After mixing, place the raw materials in a graphite crucible and melt them in a silicon carbide rod furnace at 1300℃ for 10 minutes. Pour the clear glass melt onto a graphite plate and press it into a glass sheet. Transfer the obtained glass to an annealing furnace at 480℃ for 3 hours. After cooling to room temperature in the furnace, remove the glass to obtain orange-yellow transparent borate glass. Under ultraviolet light excitation, the prepared glass sample exhibits strong near-infrared fluorescence. The emission spectrum obtained by the FLS1000 fluorescence spectrometer is a broadband emission peak with a center wavelength of 730 nm and a full width at half maximum (FWHM) of 228 nm.

[0079] Example 10#:

[0080] The preparation process of Example 10 is as follows:

[0081] Mass (g) 2.270 7.725 7.606 2.399

[0082] Table 11: Composition of the matrix glass in Example 10

[0083] First, according to the matrix glass composition in Table 11, weigh 20g of the required raw materials, including SrCO3 (2.270g) (MO introduced from SrCO3), SrF2 (7.725g) (MF2 introduced from SrF2), H3BO3 (7.606g) (B2O3 introduced from H3BO3), and Al(OH)3 (2.399g) (Al2O3 introduced from Al(OH)3). Mix all raw materials thoroughly in an agate mortar. After mixing, place the raw materials in a graphite crucible and melt them in a silicon carbide rod furnace at 1300℃ for 10 minutes. Pour the clarified glass melt onto a graphite plate and press it into a glass sheet. Transfer the obtained glass to an annealing furnace at 500℃ for 3 hours. After cooling to room temperature in the furnace, remove the glass to obtain an orange-yellow transparent borate glass. Under ultraviolet light excitation, the prepared glass sample exhibits strong near-infrared fluorescence. The emission spectrum obtained by the FLS1000 fluorescence spectrometer is a broadband emission peak with a center wavelength of 730 nm and a full width at half maximum (FWHM) of 228 nm.

[0084] Example 11#:

[0085] The preparation process of Example 11 is as follows:

[0086] Mass (g) 6.913 1.024 4.088 4.332 3.643

[0087] Table 12: Composition of matrix glass in Example 11

[0088] First, according to the matrix glass composition in Table 12, weigh 20g of the required raw materials, including BaCO3 (6.913g) (MO introduced from BaCO3), BaF2 (1.024g) (MF2 introduced from BaF2), BaSO4 (4.088g) (MSO4 introduced from BaSO4), H3BO3 (4.332g) (B2O3 introduced from H3BO3), and Al(OH)3 (3.643g) (Al2O3 introduced from Al(OH)3). Mix all raw materials thoroughly in an agate mortar. After mixing, place the raw materials in a graphite crucible and melt them in a silicon carbide rod furnace at 1100℃ for 10 minutes. Pour the clear glass melt onto a graphite plate and press it into a glass sheet. Transfer the obtained glass to an annealing furnace at 500℃ for 4 hours. After cooling to room temperature in the furnace, remove the glass to obtain an orange-red transparent borate glass. Under ultraviolet light excitation, the prepared glass sample exhibits strong near-infrared fluorescence. The emission spectrum obtained by the FLS1000 fluorescence spectrometer is a broadband emission peak with a center wavelength of 740 nm and a full width at half maximum (FWHM) of 228 nm.

[0089] Example 12#:

[0090] The preparation process of Example 12 is as follows:

[0091] Mass (g) 1.783 7.150 2.819 4.480 3.768

[0092] Table 13: Composition of the matrix glass in Example 12

[0093] First, according to the matrix glass composition in Table 13, weigh 20g of the required raw materials, including SrCO3 (1.783g), BaCO3 (7.150g) (the MO is introduced from SrCO3 and BaCO3), BaSO4 (2.819g) (the MSO4 is introduced from BaSO4), H3BO3 (4.480g) (the B2O3 is introduced from H3BO3), and Al(OH)3 (3.768g) (the Al2O3 is introduced from Al(OH)3). Mix all raw materials thoroughly in an agate mortar. After mixing, place the raw materials in a graphite crucible and melt them in a silicon carbide rod electric furnace at 1200℃ for 40 minutes. Pour the clear glass melt onto a graphite plate and press it into a glass sheet. Transfer the obtained glass to an annealing furnace at 480℃ for 3 hours. After cooling to room temperature in the furnace, remove the glass to obtain an orange-red transparent borate glass. Under ultraviolet light excitation, the prepared glass sample exhibits strong near-infrared fluorescence. The emission spectrum obtained by the FLS1000 fluorescence spectrometer is a broadband emission peak with a center wavelength of 740 nm and a full width at half maximum (FWHM) of 228 nm.

[0094] Example 13#:

[0095] The preparation process of Example 13 is as follows:

[0096] Mass (g) 4.959 4.406 0.789 1.467 5.439 2.940

[0097] Table 14: Composition of matrix glass in Example 13

[0098] First, according to the matrix glass composition in Table 14, weigh 20g of the required raw materials, including BaCO3 (4.959g) (MO introduced from BaCO3), BaF2 (4.406g), SrF2 (0.789g) (MF2 introduced from BaF2 and SrF2), BaSO4 (1.467g) (MSO4 introduced from BaSO4), H3BO3 (5.439g) (B2O3 introduced from H3BO3), and Al(OH)3 (2.940g) (Al2O3 introduced from Al(OH)3). Mix all raw materials thoroughly in an agate mortar. After mixing, place the raw materials in a graphite crucible and melt them in a silicon carbide rod furnace at 1200℃ for 50 minutes. Pour the clarified glass melt onto a graphite plate and press it into a glass sheet. Transfer the obtained glass to an annealing furnace at 500℃ for 3 hours. After cooling to room temperature in the furnace, remove the glass to obtain an orange-yellow transparent borate glass. Under ultraviolet light excitation, the prepared glass sample exhibits strong near-infrared fluorescence. The emission spectrum obtained by the FLS1000 fluorescence spectrometer is a broadband emission peak with a center wavelength of 740 nm and a full width at half maximum (FWHM) of 228 nm.

[0099] Example 14#:

[0100] The preparation process of Example 14 is as follows:

[0101] Mass (g) 1.270 7.512 2.961 6.277 1.980

[0102] Table 15: Composition of the matrix glass in Example 14

[0103] First, according to the matrix glass composition in Table 15, weigh 20g of the required raw materials, including CaCO3 (1.270g), BaCO3 (7.512g) (MO introduced from CaCO3 and BaCO3), BaSO4 (2.961g) (MSO4 introduced from BaSO4), H3BO3 (6.277g) (B2O3 introduced from H3BO3), and Al(OH)3 (1.980g) (Al2O3 introduced from Al(OH)3). Mix all raw materials thoroughly in an agate mortar. After mixing, place the raw materials in a graphite crucible and melt them in a silicon carbide rod furnace at 1300℃ for 10 minutes. Pour the clear glass melt onto a graphite plate and press it into a glass sheet. Transfer the obtained glass to an annealing furnace at 500℃ for 3 hours. After cooling to room temperature in the furnace, remove the glass to obtain an orange-red transparent borate glass. Under ultraviolet light excitation, the prepared glass sample exhibits strong near-infrared fluorescence. The emission spectrum obtained by the FLS1000 fluorescence spectrometer is a broadband emission peak with a center wavelength of 740 nm and a full width at half maximum (FWHM) of 228 nm.

[0104] Example 15#:

[0105] The preparation process of Example 15 is as follows:

[0106] Mass (g) 4.693 5.550 1.092 5.882 2.783

[0107] Table 16: Composition of the matrix glass in Example 15

[0108] First, according to the matrix glass composition in Table 16, weigh 20g of the required raw materials, including BaCO3 (4.693g) (the MO is introduced from BaCO3), BaSO4 (5.550g), SrSO4 (1.092g) (the MSO4 is introduced from BaSO4 and SrSO4), H3BO3 (5.882g) (the B2O3 is introduced from H3BO3), and Al(OH)3 (2.783g) (the Al2O3 is introduced from Al(OH)3). Mix all raw materials thoroughly in an agate mortar. After mixing, place the raw materials in a graphite crucible and melt them in a silicon carbide rod furnace at 1200℃ for 10 minutes. Pour the clear glass melt onto a graphite plate and press it into a glass sheet. Transfer the obtained glass to an annealing furnace at 500℃ for 3 hours. After cooling to room temperature in the furnace, remove the glass to obtain an orange-red transparent borate glass. Under ultraviolet light excitation, the prepared glass sample exhibits strong near-infrared fluorescence. The emission spectrum obtained by the FLS1000 fluorescence spectrometer is a broadband emission peak with a center wavelength of 740 nm and a full width at half maximum (FWHM) of 228 nm.

[0109] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A near-infrared fluorescent glass for bioimaging, characterized in that, The glass composition has the following molar percentages: 20-50 mol% MO, 0-40 mol% MF2, 0-40 mol% MSO4, 10-40 mol% B2O3, and 10-30 mol% Al2O3, where M is one or more of the alkaline earth metals Ca, Sr, and Ba, and MF2 and MSO4 cannot both be 0.

2. The near-infrared fluorescent glass for bioimaging as described in claim 1, characterized in that, The MO alkaline earth metal oxide is BaO, and the MSO4 alkaline earth metal sulfate is BaSO4. The glass composition by molar percentage is as follows: 49.3 mol% BaO, 0.7 mol% BaSO4, 40 mol% B2O3, and 10 mol% Al2O3.

3. The near-infrared fluorescent glass for bioimaging as described in claim 1, characterized in that, The MO alkaline earth metal oxide is BaO, and the MF2 alkaline earth metal fluoride is BaF2. The glass composition is as follows (molar percentage): 20 mol% BaO, 30 mol% BaF2, 40 mol% B2O3, and 10 mol% Al2O3.

4. A method for preparing near-infrared fluorescent glass for bioimaging as described in any one of claims 1-3, characterized in that, Includes the following steps: Based on the molar percentage of the glass composition, calculate the mass of each glass component, accurately weigh each raw material, wherein the MO is introduced by MCO3, the B2O3 is introduced by B2O3 or H3BO3, and the Al2O3 is introduced by Al(OH)3 or Al2O3; grind the weighed raw materials in an agate mortar and mix them evenly to form a mixture. The mixture is placed in a high-temperature furnace and heated from room temperature to 1000℃~1300℃, and melted for 10-60 minutes under a reducing atmosphere with carbon protection. After the glass is removed, it is quickly poured onto a graphite plate to obtain a transparent glass sample. The obtained glass sample was transferred to a muffle furnace at 470℃~500℃ for annealing. After holding at this temperature for 3~5 hours, it was allowed to cool naturally to room temperature. The glass was then removed after complete cooling.

5. The method for preparing near-infrared fluorescent glass for bioimaging according to claim 4, characterized in that, The reducing atmosphere for carbon protection is achieved through one of the following methods: Using the nested crucible method, the raw material is placed in an alumina crucible, and then covered with a lid for placing carbon powder or graphite powder. Corundum crucible; Using the nested crucible method, the raw material is placed in a graphite crucible and then covered with a corundum crucible. Place the raw materials directly into a covered graphite crucible.

6. A near-infrared optical device, characterized in that: The near-infrared optical device comprises the near-infrared fluorescent glass according to any one of claims 1 to 3.

Citation Information

Patent Citations

  • Near-infrared fluorescent powder as well as preparation method and application thereof

    CN113025328A